Table tennis for patients with Parkinson's disease: A single-center, prospective pilot study. (2021) - Inoue, Kenichi; Fujioka, Shinsuke; Nagaki, Koichi; Suenaga, Midori; Kimura, Kazuki; Yonekura, Yukiko; Yamaguchi, Yoshiki; Kitano, Kosuke; Imamura, Ritsuko; Uehara, Yoshinari; Kikuchi, Hitoshi; Matsunaga, Yoichi; et al.
Highlights: This study reports the impact of table tennis exercises on Parkinson's disease. Table tennis exercise may improve motor symptoms of Parkinson's disease. Table tennis exercise may improve ADL of patients with Parkinson's disease. Table tennis exercise is safe for Parkinson's disease patients. Abstract: Introduction: Table tennis is a popular sport worldwide. However, no study has examined whether it is an effective exercise for patients with Parkinson's disease (PD). The efficacy and safety of table tennis exercise for PD patients was examined. Methods: This 6-month prospective study investigated if our table tennis exercise program could improve parkinsonian motor symptoms, cognition and psychiatric symptoms. Twelve PD patients with Hoehn & Yahr stage ≤4 were recruited. Patients participated in a 6-hour exercise session once weekly. All patients were assessed with the Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS) parts I-IV, Montreal Cognitive Assessment (MoCA), Frontal Assessment Battery (FAB), Self-Rating Depression Scale (SDS), and Starkstein Apathy Scale (SAS) at baseline, 3 months, and 6 months. Results: Nine of 12 PD patients were analyzed, except for three patients for which data was missing. MDS-UPDRS parts II and III were improved at 3 months (median −4.0, p = 0.012 and median −10.0, p = 0.012) and 6 months (median −7.0, p = 0.015 and median −12.0, p = 0.008), whereas MDS-UPDRS total parts I scores and total IV scores, MoCA, FAB, SDS, and SAS were unchanged. Adverse events included fall and backache in one patient each. Conclusion: A table tennis exercise program is relatively safe and may improve activities of daily living and motor symptoms in patients with PD.